Establishing strong brand equity with consumer-based approach for Malaysian fashion brands’ growth in fast-fashion industry / Siti Fatimah Hashim - Hashim, Siti Fatimah (2021)
Fast-Fashion industry has endlessly offered the latest trends in a competitive short production-cycle. Albeit rapid expansion, Malaysian Fashion Brands have faced fierce competitions especially from international counterparts to indicate that they were perceived weak in brand equity perspectives. MFBs’ businesses are downward due to intense competitions and unpredictable consumer behaviour thus, affecting their growth. The study aims to find how consumers perceive MFBs’ brand equity and what factors can contribute to the outcome. The main research objective is to investigate whether Consumer-Based Approach (CBA) can significantly predict Strong Brand Equity in a relationship-based research. The main strategies of this study are by using CBA model to measure the level of Brand Equity perceived in Malaysian consumer market, systematic data collection procedures and statistical analysis to obtain inferential results. CBA Model is adapted from Consumer-based brand equity Model (Keller, 1993) postulated in Independent Variables of Brand Awareness, Brand Image and Purchase Intention to predict Strong Brand Equity as the Dependent Variable. In addition, Community Engagement and Brand Loyalty are examined whether can have moderated mediation indirect effects on the cause-effect relationships. Quantitative research method was employed where 6 constructs and 17 latent variables were designed into 99 instrumental scales. The datasets were collected through a non- probability convenient sampling technique with success response rate of 29.7% via both online and offline survey tools. After data screening procedures, 798 cleaned datasets are utilized for further statistical analysis where SPSS version 25 for Descriptive Analysis and SmartPLS version 3.2.8 for Measurement and Structural Model Analysis. The findings show that Brand Loyalty has full mediating effects meanwhile, Community Engagement has no moderated mediation indirect effect on the causal relationships. The overall results indicate that MFBs are perceived low in brand equity which interpreted as lacking of competitive advantages thus, jeopardizing their brand health and business progression. The findings have implications on the existing body of knowledge as they contradict to the previous findings of past literatures. Future studies should look at other factors to trigger consumer behaviour in giving effects towards strong brand equity establishment for MFBs’ business outgrowth.